National endogenous science and technology capacity: Current situation and solutions - Nguyen Ke Nghia (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
The process of industrialization and modernization in Vietnam has been carried out for quite a long time. Only since the country's reunification (1976) until now, the industrialization process has taken place for nearly 50 years. Despite of achieving great and historically significant milestones and robust comprehensive development compared to pre-reform years”, Vietnam has recently transitioned to a lower-middle income country. Vietnam is striving, by 2025, to surpass the lower-middle income threshold, become an upper-middle income country by 2030, and become a developed, high-income country by 2045. To accomplish this goal, the 13th National Party Congress outlined the task of “Continuing to promote industrialization and modernization on the foundation of scientific, technological and innovation progress”. Within the scope of this article, the author presents various aspects of solutions to enhance the nation's endogenous science and technology capacity, contributing to the task of industrialization and modernization advancement, based on the progress of science, technology, and innovation. Code: 23091401